HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN TINGKAT PENGETAHUAN TENTANG KEKERASAN BERBASIS GENDER ONLINE (KBGO) PADA GENERASI Z DI KOTA PADANG - Juni Santri Hasibuan; Vitania Yulia (Departemen Ilmu Komunikasi Universitas Andalas, 2026)
The high number of cases of Online Gender-Based Violence (OGBV) in Padang City indicates that many individuals are still unaware of and unaware of such violent behavior. This study was conducted to determine the relationship between social media use and the level of knowledge of OGBV among Generation Z in Padang City. This study used a survey research method by distributing questionnaires to 384 respondents spread across Padang City. The Knowledge Gap Theory by Philip J. Tichenor, George A. Donohue, and N. Olien was used in analyzing the research. The data analysis used Spearman Rank Correlation Analysis using the SPSS application. The results of the study indicate that overall, Generation Z's social media use in Padang City shows great potential through high communication skills and selective exposure. Meanwhile, the level of respondents' knowledge about OGBV is in the five indicators that reach a high level of knowledge: revenge porn in the highest position, cyber hacking, sextortion, cyber grooming, and impersonation. Medium scores on two indicators: cyber harassment and cyber recruitment. And finally, four indicators score low: cyber stalking, malicious distribution, morphing and online defamation as the lowest. Based on the results of the Spearman rank correlation test, there is a strong relationship between the use of social media and the level of knowledge about KBGO with a correlation coefficient of 0.612.